2019
DOI: 10.3390/molecules25010043
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Antioxidant Activity, Profile, and Content of Polyphenols and Tocopherols in Common Hazel Seed (Corylus avellana L.) Depending on Variety and Harvest Date

Abstract: The aim of the study was to evaluate the influence of variety and the date of harvest of hazelnut seeds on their antioxidant potential and the profile and content of polyphenols and tocopherols. The research material included the hazelnut seeds of six varieties, harvested from July to September at equal 30-day intervals. Hazelnuts were analyzed for total fat content and antioxidant properties, whereby UPLC-PDA-ESI-MS analysis was used to determine the profile and content of polyphenols, and the HPLC method to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
15
1
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 29 publications
4
15
1
6
Order By: Relevance
“…Walnuts are a rich source of polyunsaturated fatty acids; they show the most favorable ratio of n-6 and n-3 fatty acids, which should be 4:1. Hazelnuts and almonds, on the other hand, are an excellent source of vitamin E [ 9 ]. As reported by Kornsteiner et al [ 10 ], a portion of hazelnuts (42 g) provides over 100% of the recommended daily intake of vitamin E, thanks to which the body is protected against free radicals, thus preventing the aging process, the development of atherosclerosis and cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Walnuts are a rich source of polyunsaturated fatty acids; they show the most favorable ratio of n-6 and n-3 fatty acids, which should be 4:1. Hazelnuts and almonds, on the other hand, are an excellent source of vitamin E [ 9 ]. As reported by Kornsteiner et al [ 10 ], a portion of hazelnuts (42 g) provides over 100% of the recommended daily intake of vitamin E, thanks to which the body is protected against free radicals, thus preventing the aging process, the development of atherosclerosis and cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Walnuts are the richest source of polyunsaturated fatty acids and have the most favorable ratio of n-6 and n-3 fatty acids, Foods 2020, 9, 1081 2 of 13 which should be 4:1. Hazelnuts and almonds are an excellent source of vitamin E [4]. According to Kornsteiner et al [5], a portion of hazelnuts (42 g) provides more than 100% of the recommended daily intake of vitamin E, so that the body is protected against free radicals, thus preventing early ageing, atherosclerosis and cancer.…”
Section: Introductionmentioning
confidence: 99%
“…The HS used in our study showed comparable (although slightly lower) content of α-tocopherol. Besides differences in analytical procedures, hazelnut varieties and harvest time have been reported as significant factors influencing the tocopherols content [49]. Regarding the effect of roasting on tocopherols content in hazelnut and its skin, contrasting results are available in literature [50].…”
Section: Chemical Composition Of Hazelnut Skinmentioning
confidence: 99%